Addressing an Undergraduate Research Issue about Normalized Change for Critical Thinking Test (Jurnal Pendidikan IPA Indonesia, 2017)
Normalized change is a familiar expression used to measure student’s improvement in physics education research, including critical thinking skill improvement. A widely used standardized critical thinking test is the Cornell Critical Thinking Test. The CCTT scoring method, rights minus one-half the number wrong, results from possible interval scores ranging from the negative minimum score to positive maximum score. The problem then arises in the use of the normalized change in CCTT scores, particularly in the situation when the post-test score is worse than the pre-test score. We reveal the used equation deficiencies and demonstrate the mistakes made by undergraduate researchers, as well as suggesting a modified equation that can be used under the normalized change rationale, i.e. the ratio of the gain or the loss of the maximum possible gain or loss. Some frequently asked questions about normalized change are also discussed.